WYBRANE ZAGADNIENIA WŁASNOŚCI ZABYTKÓW I DZIEŁ SZTUKI W PRAWIE PRL-U - Alicja Jagielska-Burduk (Zeszyty Prawnicze)
LEGAL STATUS OF CULTURAL PROPERTY AND WORKS OF ART IN THE PRL Summary The article deals with the legal status of works of art and cultural property in the Polish legislation during communism period. Classifying those objects as private property was considered as a very difficult task, because of their material value and the public interest in saving them for future generations. The strict limitations of individuals property were perceived as unusual and as a result a new sort of property – the private cultural property was distinguished. Moreover, the concepts of the common heritage and res extra commercium could be observed in the light of the PRL ideas. It should be emphasized that the above mentioned theories for improving cultural heritage regulations are the most popular in the nowadays’ international discussion.